Kewaspadaan Terhadap Musuh Tersamarkan Dalam Komunitas Kristen: Analisis Alkitabiah Terhadap Ancaman Penyesat Dan Nabi Palsu - Gunarto, Rita Oktavia; Herman, Samuel; Abraham, Jessica Elizabeth (REAL DIDACHE: Journal of Christian Education, 2024)
True Christians build their faith on personal decisions born from spiritual experiences, particularly their belief in Jesus Christ. However, some individuals may join with impure motives, like yeast hidden in dough, which can negatively influence the community. This group includes deceivers, false prophets, and hypocrites who disguise themselves as fellow believers but are, in fact, hidden enemies. In Matthew 16:5-12, Jesus warns His disciples to be vigilant against the "yeast" representing the teachings of the Pharisees and Sadducees. This study employs a qualitative approach and literature review to explore strategies for being vigilant against such symbolic "yeast." It offers concrete guidelines on how to protect Christian communities from harmful elements. The analysis outlines vigilance strategies based on biblical principles, helping Christians uphold the quality of their faith and bear the fruits of righteousness. By His grace, true Christians are expected to be effective witnesses for Christ and overcome deceptive efforts in the end times. Keywords: christian vigilance; gospel of matthew 16; threats of false teachingAbstrakOrang Kristen sejati membangun iman mereka berdasarkan keputusan pribadi yang lahir dari pengalaman spiritual, khususnya keyakinan kepada Tuhan Yesus. Namun, ada individu yang bergabung dengan motif tidak murni, seperti ragi yang tersembunyi dalam tepung, yang dapat merusak komunitas. Kelompok ini termasuk penyesat, nabi palsu, dan munafik yang menyamar sebagai saudara seiman tetapi sebenarnya adalah musuh terselubung. Dalam Matius 16:5-12, Tuhan Yesus mengingatkan murid-murid-Nya untuk waspada terhadap "ragi" yang melambangkan ajaran orang Farisi dan Saduki. Penelitian ini menggunakan pendekatan kualitatif dan studi pustaka untuk mengeksplorasi strategi kewaspadaan terhadap ancaman "ragi" simbolis tersebut. Tulisan ini memberikan panduan konkret tentang bagaimana menjaga komunitas Kristen dari elemen perusak. Analisis ini menawarkan strategi kewaspadaan berdasarkan prinsip Alkitab, membantu orang Kristen menjaga kualitas iman dan menghasilkan buah kebenaran. Dengan anugerah-Nya, diharapkan mereka dapat menjadi saksi Kristus yang kuat dan mengatasi upaya penyesatan di akhir zaman.Kata Kunci: ancaman ajaran sesat; injil matius 16; kewaspadaan kristenTrue Christians build their faith on personal decisions born from spiritual experiences, particularly their belief in Jesus Christ. However, some individuals may join with impure motives, like yeast hidden in dough, which can negatively influence the community. This group includes deceivers, false prophets, and hypocrites who disguise themselves as fellow believers but are, in fact, hidden enemies. In Matthew 16:5-12, Jesus warns His disciples to be vigilant against the "yeast" representing the teachings of the Pharisees and Sadducees. This study employs a qualitative approach and literature review to explore strategies for being vigilant against such symbolic "yeast." It offers concrete guidelines on how to protect Christian communities from harmful elements. The analysis outlines vigilance strategies based on biblical principles, helping Christians uphold the quality of their faith and bear the fruits of righteousness. By His grace, true Christians are expected to be effective witnesses for Christ and overcome deceptive efforts in the end times. Keywords: christian vigilance; gospel of matthew 16; threats of false teaching